Integrating Tree Diagram Technique into Vocabulary Teaching in EFL Settings - Novia Irhana Ramadhani; Arni Arsyad Sultan; Ilyas; Lewi Kabanga (Media Publikasi Cendekia Indonesia, 2026)
This study investigates the effectiveness of the Tree Diagram Technique in improving junior high school students’ mastery of basic English vocabulary in Indonesia. Vocabulary plays an essential role in language acquisition; however, many students experience difficulties in learning new words due to monotonous instructional methods. The Tree Diagram Technique, as a visual learning strategy, helps students organize vocabulary into meaningful categories, thereby supporting comprehension and memory retention. This study employed a quantitative approach using a one-group pretest–posttest design. The participants were 25 eighth-grade students of a junior high school in Bone Regency. Data were collected through a 20-item vocabulary test administered before and after the treatment. The results of the Wilcoxon signed-rank test revealed a statistically significant improvement in students’ vocabulary achievement, with the mean score increasing from 51.4 in the pretest to 82.4 in the posttest (p < 0.05). These findings indicate that the Tree Diagram Technique is an effective instructional strategy for enhancing students’ vocabulary mastery in EFL classrooms. The study also contributes to EFL pedagogy by demonstrating the potential adaptation of the Tree Diagram Technique from syntactic analysis into engaging and visually organized vocabulary instruction.